Trial of labor after cesarean in older women who never delivered vaginally. (February 2020) - Levin, Gabriel; Mankuta, David; Yossef, Ezra; Yahalomy, Shlomo Z.; Meyer, Raanan; Elchalal, Uriel; Yagel, Simcha; Rottenstreich, Amihai
Abstract: Objective: Maternal age is an established determinant of successful trial of labor after cesarean (TOLAC). While an increasing proportion of parturients are aged 40 years and older, and previously underwent a cesarean section, little data regarding TOLAC success for this age group is available. This study assessed TOLAC success, and its associated characteristics, among women > 40 years who never delivered vaginally. Study design: A retrospective case-control study of all women who never delivered vaginally aged ≥40 years with a history of previous cesarean delivery, who delivered at our hospital during 2006-2017. Maternal, neonatal, and delivery characteristics were compared between women with successful and unsuccessful TOLAC. Results: Of 335 older women who never delivered vaginally with a history of one cesarean delivery, 61 (18.2 %) elected TOLAC (18.2 %); the median age was 41[40–42] years and the inter-delivery interval 34 [25–50] months. Overall, 38/61 (62.3 %) had a successful TOLAC. Women with successful TOLAC had a higher rate of a non-recurrent indication for cesarean delivery in their previous cesarean delivery (42.1 % vs. 13.0 %, P = 0.01), whereas dysfunctional labor at previous delivery was more common in the failed TOLAC group (47.8 % vs. 15.8 %, P = 0.007). Failed TOLAC was associated with the presence of gestational diabetes (13.0 % vs. 0 %, P = 0.02) and having a comorbidity (47.8 % vs. 21.0 %, P = 0.02). Induction of labor at TOLAC was more common in the failed TOLAC group (34.8 % vs. 2.6 %, P < 0.001). Birthweight was higher in the failed TOLAC group (3330 vs. 3107 g, P = 0.04), as well as the birthweight difference between deliveries (212 g vs. 82 g, P = 0.03). Neonatal and maternal outcomes were comparable between groups, except for longer length of stay (5 vs. 4 days, P = 0.04) in the failed TOLAC group. In a multivariable logistic regression analysis, only two factors were independently associated with TOLAC failure: previous cesarean delivery due to dysfunctional labor (OR [95 % CI]: 13.40 (1.29, 138.71), P = 0.03) and higher inter-delivery birthweight difference (OR [95 % CI]: 1.18 (1.11, 1.39), P = 0.02). Conclusions: TOLAC in older women who never delivered vaginally is associated with a moderate success rate. The indication for cesarean delivery at the first delivery and inter-delivery birthweight difference were identified as having strong predictive value for TOLAC outcome.